2016
DOI: 10.1123/jab.2015-0024
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Torso Motion in Tethered Front Crawl Stroke and its Implications on Low Back Pain

Abstract: Low back pain is a common problem among competitive swimmers, and repeated torso hyperextension is claimed to be an etiological factor. The purpose of this study was to describe the three-dimensional torso configurations in the front crawl stroke and to test the hypothesis that swimmers experience torso hyperextension consistently across the stroke cycles. Nineteen collegiate swimmers underwent 2 measurements: a measurement of the active range of motion in 3 dimensions and a measurement of tethered front crawl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…The temporal variables and kinematic variables determined in the present study are within the ranges reported in literature 26,27,32,34,39 and the scapular motions and shoulder (scapulohumeral) joint angles presented here are consistent with the corresponding values in the literature 15,16 . Furthermore, the validity of measuring the mid‐torso joint angle with the same measurement system was tested and confirmed elsewhere 18 . The good agreement between the numerical results obtained in the present study and those in the literature indicates the validity of the present data collection method and the validity of the results obtained from our kinematic analysis of pitching motion.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The temporal variables and kinematic variables determined in the present study are within the ranges reported in literature 26,27,32,34,39 and the scapular motions and shoulder (scapulohumeral) joint angles presented here are consistent with the corresponding values in the literature 15,16 . Furthermore, the validity of measuring the mid‐torso joint angle with the same measurement system was tested and confirmed elsewhere 18 . The good agreement between the numerical results obtained in the present study and those in the literature indicates the validity of the present data collection method and the validity of the results obtained from our kinematic analysis of pitching motion.…”
Section: Discussionsupporting
confidence: 90%
“…15,16 Furthermore, the validity of measuring the mid-torso joint angle with the same measurement system was tested and confirmed elsewhere. 18 The good agreement between the numerical in the present study and those the literature indicates the validity of the present data collection method and the validity of the results obtained from our kinematic analysis of pitching motion.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Body landmarks for the thorax, scapulae, humeri, and joint coordinate systems for the shoulder were defined according to ISB recommendations 16) . Body landmarks for the pelvis and joint coordinate systems for the low back were defined according to a previous study 17) . Body landmarks for the head were chosen as the vertex of the head and the left and right tragions.…”
Section: Body Posture Measurementmentioning
confidence: 99%